The Political Economy of Local Content Requirements Policy in Indonesia’s Telecommunication Manufacturing Industry 2015-2020 - Al-Fadhat, Faris; Handana, Praba Satya (Nation State: Journal of International Studies, 2023)
This article examines the factors shaping Indonesia’s Local Content Requirements (LCR) policy on the telecommunications manufacturing industry, specifically on the production of smartphones from 2015 to 2020. The LCR policy mandates both foreign and domestic corporations to utilize local content up to a specified minimum threshold. The Indonesia’s LCR policy on the telecommunications industry is set at a minimum of 30%. This local content could be derived from labor, raw materials for product manufacturing, or investment. Nevertheless, the implementation of the Indonesia’s LCR policy is considered contradictory to the previous government’s endeavors to augment the level of foreign direct investment. This is because the LCR policy is seen as a protectionist measure that may potentially hinder foreign companies, thereby inducing a decrease in investment. This study applies a political economy approach with library research data collection methods and subsequently analyzed using qualitative methods. The result of this research shows that the Indonesian government’s LCR policy is underpinned by two primary factors and interests. Firstly, it aims to support corporate interests, particularly the development of the local telecommunications industry. Secondly, the policy is motivated by a long-term ambition to increase the participation of Indonesian businesses in Global Value Chain (GVC) networks.